In Vitro and In Vivo Pharmacological Profiles of DS‐1211, a Novel Potent, Selective, and Orally Bioavailable Tissue‐Nonspecific Alkaline Phosphatase Inhibitor. (13th September 2022) - Soma, Kaori; Izumi, Masanori; Yamamoto, Yuko; Miyazaki, Shojiro; Watanabe, Kengo
ABSTRACT: Inhibition of tissue‐nonspecific alkaline phosphatase (TNAP) may prevent ectopic soft tissue calcification by increasing endogenous pyrophosphate (PPi). DS‐1211 is a potent and selective novel small molecule TNAP inhibitor with well‐characterized pharmacokinetics (PKs) in rodent and monkey. Herein, we report a comprehensive summary of studies establishing the pharmaceutical profile of DS‐1211. In vitro studies characterized the mode of inhibition and inhibitory effects of DS‐1211 on three human alkaline phosphatase (ALP) isozymes—TNAP, human intestinal ALP, human placental ALP—and on ALP activity across species in mouse, monkey, and human plasma. In vivo PK and pharmacodynamic (PD) effects of a single oral dose of DS‐1211 in mice and monkeys were evaluated, including biomarker changes in PPi and pyridoxal 5′‐phosphate (PLP). Oral bioavailability (BA) was determined through administration of DS‐1211 at a 0.3‐mg/kg dose in monkeys. In vitro experiments demonstrated DS‐1211 inhibited ALP activity through an uncompetitive mode of action. DS‐1211 exhibited TNAP selectivity and potent inhibition of TNAP across species. In vivo studies in mice and monkeys after single oral administration of DS‐1211 showed linear PKs, with dose‐dependent inhibition of ALP activity and increases in plasma PPi and PLP. Inhibitory effects of DS‐1211 were consistent in both mouse and monkey. Mean absolute oral BA was 73.9%. Overall, in vitro and in vivo studies showed DS‐1211 is a potent and selective TNAP inhibitor across species. Further in vivo pharmacology studies in ectopic calcification animal models and clinical investigations of DS‐1211 in patient populations are warranted. © 2022 Daiichi Sankyo, Inc. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).